Surgical management of 58 patients with placenta praevia percreta - (:unkn) unknown (SPRINGER WIEN, 2016)
The aim of this study is to present our experience with surgical management of placenta praevia percreta. This study was conducted from January 2009 through March 2014 at Harran University Hospital and was a chart review of all patients who underwent caesarean hysterectomy with the placenta left in situ for placenta praevia percreta. The study group comprised 58 patients. All of the patients underwent ultrasound mapping of the placental area before surgery. Emergent caesarean hysterectomy was only performed in 9 patients; 49 patients underwent planned caesarean hysterectomy. Bilateral internal iliac artery ligation was performed in all cases. Four patients (6.9 %) had bladder damage, one patient (1.7 %) required cystotomy, and one patient (1.7 %) required re-operation because of postoperative hemorrhage. The mean operative time was 141.6 (range: 95-355) minutes. Only 17 (29.3 %) patients were administered more than four units of red blood cells. There was no ureteral damage or maternal death. Furthermore, there were no complications in 42 (72.4 %) patients. Caesarean hysterectomy for placenta praevia percreta is associated with increased maternal morbidity. However, preoperative diagnosis of placenta praevia percreta, ultrasound mapping of the placenta, and the presence of a multidisciplinary experienced team may decrease maternal morbidity and mortality. Moreover, the urinary system may be protected in the patients with placenta praevia percreta without serious morbidity.
Keywords: Placenta percreta; Placenta praevia; Obstetric hemorrhage; Caesarean hysterectomy; MASSIVE POSTPARTUM HEMORRHAGE; ACCRETA; OUTCOMES; BLADDER; BALLOON